ADVERSE EVENTS IN THE ICU CAN BE ERADICATE THROUGH CONTINUING EDUCATION - Sobral Silva do Nascimento, Andresa; Alessandro Florentino de Andrade, Wesley (Health and Society, 2023)
Introduction: To analyze publications in the context of adverse events in the intensive care unit (ICU) and the effects of continuing and continuing education on these events. Objective: To know how continuing education has contributed to the reduction of cases of adverse events in intensive care units in published literature. Methods: this is a bibliographic review, carried out in the Virtual Health Library and legal documents published between 2019 and 2020, considering those whose access to the journal was free to the full texts and in Portuguese. Articles that did not directly address the topic in question were excluded. Results: 1459 articles were found and only four remained, which met the research inclusion criteria. Conclusion: And the bodies responsible for investigating and punishing such events may understand that errors are underreported due to the punitive and non-educational culture and from this to further support the educational process, promoted by continuing education as well as observe the lack of trained professionals to assume to institute a safe assistance.